Pengaruh Pemahaman Dan Kepatuhan Wajib Pajak UMKM Terhadap Pendapatan Asli Daerah Kabupaten Maros - Nuryanti Nurman; Karmilah Karmilah (Program Studi Administrasi Fiskal, 2026)
This study aims to examine the influence of understanding and compliance of Micro, Small, and Medium Enterprises (MSMEs) taxpayers on the Local Original Revenue in Maros Regency. The research employs a quantitative method with data collection through questionnaires distributed to MSME actors and revenue agency staff. Data analysis was conducted using multiple linear regression software (SPSS) to test the impact of both variables on Local Original Revenue. The findings indicate that taxpayer compliance has a significant effect on increasing local revenue, whereas the level of tax understanding does not have a direct impact. The conclusion emphasizes that improving MSMEs taxpayer compliance can support the enhancement of regional revenue. The implications of this study highlight the importance of effective taxation education and socialization strategies to promote taxpayer compliance among MSMEs